Stress Analysis of Pelton Bucket Using Mechanical APDL - Sonendra; Agarwal, Naman; Deshmuk, T.S. (Asian Journal of Engineering and Applied Technology, 2015)
In the present work an attempt has been made to analyse the stress developed on the surface of Pelton bucket using Mechanical APDL. The geometric modelling of this bucket has been done using CATIA software for a 50 m head and stress analysis has been done in Mechanical APDL. The stress analysis has been done considering bucket as a cantilever element fixed to the disc at one end with the force of jet applied at the splitter. The stress analysis has been done for flow rates ranging from 100 lit/sec to 150 lit/sec and speed ranging from 700 rpm to 900 rpm. It is observed that 1st principle stress is higher than 2nd principle stress and 3rd principle stress. Von Mises stress as well as all three principle stresses decreases as rotational speed of pelton wheel increases.